Investment Feasibility Analysis of Water Storage Service (WSS) in Urban - Muhammad Olik Abdul Holik; Heri Suprapto; Andi Asnur Pranata (Green Publisher Indonesia, 2025)
This study examines the feasibility of investing in a Water Storage Service (WSS) in Depok City to address the growing demand for clean drinking water. The research evaluates WSS's financial viability and sustainability, considering market, technical, financial, environmental, management, and legal aspects. Using a quantitative approach, the study employs investment evaluation criteria such as Net Present Value (NPV), Return on Investment (ROI), Internal Rate of Return (IRR), Payback Period, and Net Benefit-Cost Ratio (Net B/C). The findings indicate that the WSS initiative is financially feasible, with a positive NPV of IDR 116,553,085,906.00, ROI of 15.3, IRR of 32.06%, and a payback period of 5.7 years. Sensitivity analysis shows that the project remains viable even with a 15% reduction in sales and a 20% increase in operating costs. Despite the promising financial results, several risks were identified, including market, technical, regulatory, and business risks. The implications of this study suggest that WSS can be an effective solution to reduce reliance on bottled water and groundwater, while providing affordable, sustainable water access for Depok’s growing urban population. Future research should explore how WSS can be implemented in other urban areas facing similar water scarcity issues.